Implikasi Hukum Perkawinan di Bawah Tangan Terhadap Pencatatan Akta Kelahiran Anak - Lidwina Tuto Ladjar; Shelomita Putri Amelia; Aurelya Putri Alzahrah; Meidina Aulia; Deliana Rinasari Ghufriani; Dwi Aryanti Ramadhani (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This study aims to analyze law enforcement efforts against under-aged marriages in Indonesia, identify factors that cause under-aged marriages in Indonesia, and find out the implications of law enforcement efforts against under-aged marriages on child birth certificate registration. The research method used in this article is normative legal research which is analyzed qualitatively with a statutory approach and a case approach. The results of this study show that marriages that are only carried out based on religious law or beliefs, without being officially registered, are legal in religion, but not in the state. Factors that cause underhanded marriages include economic factors, social factors, psychological factors, and religious factors. The legal consequences caused by underhand marriages are detrimental to women and children resulting from these underhand marriages, one of which is difficulty in managing the registration of children's birth certificates. This study concludes that siri marriage/underhand marriage is recognized as religiously valid in Indonesia, but has no legal force because it is not registered at the KUA/Civil Registry in accordance with Law No. 1 of 1974. As a result, the marriage has no legal consequences for the couple and their children.